Odpowiedzi

  • Użytkownik Zadane
2010-03-03T16:58:50+01:00
A) (-3,4) * 6,1+(-3,4) * 3,9 = -20,74 - 13,26 = 34
b) (-2) * 5,1+(-2) * 3,4+(-2) * 4,7 = -10,2 - 6,8 = -17
c) 6,4 * (-4,5)+6,4 * (-3) - 6,4 * 3 = -28,8 - 19,2 = -48
d) (-5,2) * (-1,8) + (-1,8) * 3,7 - (1,8) * (-5,2)= 9,36 - 6,66 = 2,7
2010-03-03T17:04:06+01:00
A)(-3,4) * 6,1+(-3,4) * 3,9=-20,74+13,26=-34
b) (-2) * 5,1+(-2) * 3,4+(-2) * 4,7 =-10,2-6,8-9,4= -26,4
c) 6,4 * (-4,5)+6,4 * (-3) - 6,4 * 3= -28,8-19,2-19,2= -67,2
d) (-5,2) * (-1,8) + (-1,8) * 3,7 - (1,8) * (-5,2)=9,36-6,66+9,36=12,06